Experimental identification and associated model of the dissipation in the electric cables of a satellite structure. (24th November 2015) - Cluzel, C.; Rouch, P.; Dorival, O.; Behar, S.
Abstract: This paper presents a first experimental identification of the effects of electric cables on the damping of a satellite structure. The dissipation due to both the curvature of the cables and the slippage of the cables in their fasteners was taken into account based on classical plate kinematics. In order to validate a damping model for the cables, we developed tests to quantify the influence of the amplitude of the movement on the energy dissipated. Two cable sizes and three cable fastener heights were tested using a specific setup which made the curvature uniform along the whole length of the cables. The results show that while the dissipation is a function of the curvature the specific damping capacity is almost constant. However, the dissipation differs depending on the type of cable. Very small cables do not dissipate at all, but large cables can induce significant damping depending on the mode of vibration concerned.